High-corrosion-resistance plastic and preparation method thereof
By introducing surface fluorinated nano-silica-multi-walled carbon nanotube composites and aminated nanocrystalline cellulose anti-corrosion modifiers into plastics, the problem of insufficient corrosion resistance of traditional plastic products is solved, high corrosion resistance and stable mechanical properties are achieved, and it is suitable for applications in special environments.
Patent Information
- Application Number
- CN202510851809.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-24
- Publication Date
- 2025-09-12
AI Technical Summary
Traditional plastic products have weak corrosion resistance when exposed to chemicals such as acids, alkalis, and salts, and the connection performance between inorganic fillers and resin base materials is limited, resulting in low mechanical properties of plastic products, easy cracking, and inability to meet application requirements in special environments.
An anti-corrosion modifier composed of a surface fluorinated nano-silica-multi-walled carbon nanotube composite and aminated nanocrystalline cellulose is used to construct a multi-level synergistic anti-corrosion network in a polypropylene resin base material, thereby enhancing the interface bonding strength and dispersion uniformity and forming a dense anti-corrosion barrier.
It significantly improves the corrosion resistance and mechanical properties of plastics, extends their service life, and is suitable for special environments such as chemical pipelines and marine equipment.
Smart Images

Figure CN120623638A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of polymer materials, and specifically relates to a plastic with high corrosion resistance and a preparation method thereof. Background Art
[0002] With the development of society and advancements in science and technology, plastic products have been widely used in various fields. Due to their advantages such as light weight, corrosion resistance, excellent insulation, and low cost, plastics play an important role in industries such as packaging, construction, automobiles, electronics, and chemicals. However, traditional plastics also have some drawbacks in practical applications, particularly in terms of corrosion resistance.
[0003] Conventional plastics are susceptible to chemical reactions when exposed to chemicals such as acids, bases, and salts, leading to performance degradation, such as reduced strength, brittleness, surface corrosion, softening, and increased porosity. This significantly limits the application of plastics in specialized environments, such as chemical pipelines, marine equipment, and acid and alkali storage containers. Furthermore, some plastics are susceptible to environmental factors such as ultraviolet light and oxygen over long-term use, accelerating their aging process and further reducing their corrosion resistance.
[0004] In the existing technology, in order to improve the corrosion resistance and mechanical properties of plastics, anti-corrosion fillers are often added to the plastic base material. However, the connection performance between traditional anti-corrosion fillers and the plastic base material is limited. During the modification process of the plastic base material, the filler is prone to uneven dispersion, the mechanical properties of the plastic products are low, and they are prone to cracking during use, further accelerating the aging of the plastic. Therefore, improvements are urgently needed to meet the market demand for high-performance corrosion-resistant plastics. Summary of the Invention
[0005] In order to solve the technical problems in the prior art that traditional plastic products have weak acid, alkali and salt corrosion resistance, and after the resin base material is modified by traditional inorganic fillers, the connection performance between the inorganic fillers and the resin base material is weak, and the inorganic fillers are easily unevenly dispersed. After the plastic products are made, their mechanical properties are low, and they are prone to cracking during use, further accelerating the aging of the plastic products, and cannot meet the current market requirements for the energy absorption of plastic products, this application proposes a high corrosion-resistant plastic.
[0006] In order to solve the technical problem raised in this application, this application also proposes a plastic with high corrosion resistance and a preparation method thereof.
[0007] The present application adopts the following scheme: a high corrosion resistance plastic, which is composed of the following components by weight: 55-65 parts of polypropylene resin base material, 2-5 parts of dispersant, 5-8 parts of toughening agent, 8-10 parts of filler, 8-10 parts of silicone and 15-20 parts of anti-corrosion modifier;
[0008] The anti-corrosion modifier is obtained by mixing the first component and the second component in a mass ratio of (2.2-3.5):1;
[0009] The first component is a nano-silica-multi-walled carbon nanotube composite;
[0010] The second component is aminated nanocrystalline cellulose;
[0011] The first component is surface-fluorinated.
[0012] In some possible embodiments,
[0013] The preparation method of the first component comprises the following steps:
[0014] Step 101. Multi-walled carbon nanotubes and ultrapure water are placed in an ultrasonic reactor in a volume ratio of 1:(150-180) and dispersed for 35 minutes at room temperature and an ultrasonic frequency of 18 kHz to 20 kHz to obtain activated multi-walled carbon nanotubes.
[0015] Step 102. The activated multi-walled carbon nanotubes prepared in step 101 are transferred to a stirred tank. A silicon source is added dropwise to the activated multi-walled carbon nanotubes at room temperature and 1200-1600 rpm. After the silicon source is added, the reaction system is transferred to an ultrasonic reactor and reacted at room temperature, -0.01 MPa, and 22-25 kHz for 2-5 hours to obtain a crude first component.
[0016] Step 103. The crude first component prepared in step 102 is transferred to a magnetic stirring vessel and stabilized at room temperature and 300-600 rpm for 12-24 hours to obtain a stabilized crude first component.
[0017] Step 104. The stabilized crude first component prepared in step 103 is transferred to a centrifuge, the supernatant is removed, and the lower solid phase is washed with anhydrous ethanol, dried and ground to obtain the finished first component.
[0018] In some possible embodiments,
[0019] In step 101 , the multi-walled carbon nanotubes are hydroxylated multi-walled carbon nanotubes, and the inner diameter of the multi-walled carbon nanotubes is 3 nm to 5 nm, the outer diameter is 8 nm to 15 nm, and the length is 48 μm to 56 μm.
[0020] In some possible embodiments,
[0021] In step 102, the silicon source is obtained by mixing deionized water, anhydrous ethanol, and tetraethyl silicate in a mass ratio of 1: (3.5-5.5): (4.2-6.5).
[0022] In some possible embodiments,
[0023] In step 102 , the volume ratio of the silicon source to the activated multi-walled carbon nanotubes is 1:(10-15).
[0024] In some possible embodiments,
[0025] The surface fluorination modification treatment of the first component includes the following steps:
[0026] Step 201. The first component and anhydrous ethanol are sequentially added into an ultrasonic dispersion vessel at a mass ratio of 1:(20-25), and dispersed for 20 minutes at room temperature and an ultrasonic frequency of 18 kHz to 20 kHz to obtain the activated first component;
[0027] Step 202. The activated first component prepared in step 201, ultrapure water, acetic acid, and perfluorooctyltriethoxysilane are sequentially added to a stirred tank, and reacted in a water bath at 60°C-85°C and 500-800 rpm for 5-10 hours to obtain a crude fluorinated first component.
[0028] Step 203. The crude fluorinated first component prepared in step 202 is transferred to a centrifuge, the supernatant is removed, and the lower solid phase is washed, filtered, and dried in sequence to obtain the finished fluorinated first component.
[0029] In some possible embodiments,
[0030] The preparation method of the second component comprises the following steps:
[0031] Step 301. Nanocellulose crystals and anhydrous ethanol are sequentially added into an ultrasonic reactor at a mass ratio of 1:(15-20), and dispersed at room temperature and an ultrasonic frequency of 18 kHz to 20 kHz for 40 minutes to obtain activated nanocellulose crystals;
[0032] Step 302: Transfer the activated nanocellulose crystals prepared in step 301 to a centrifuge, centrifuge at 8000-10000 rpm, remove the supernatant, and retain the solid phase at the bottom;
[0033] Step 303. The lower solid phase obtained by centrifugation in step 302, anhydrous ethanol, hexadecyltrimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine and ammonia water are sequentially added into a magnetic stirring kettle, reacted for 1 h to 5 h in a nitrogen atmosphere, a water bath at 40°C to 50°C, and 2200 rpm to 2800 rpm, and then filtered, washed and dried in sequence to obtain the second component product.
[0034] In some possible embodiments,
[0035] In step 303, the mass ratio of the lower solid phase, anhydrous ethanol, hexadecyltrimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine and ammonia water is 1:(15-18):(5-8):(5-8):(2-5).
[0036] In some feasible embodiments, the filler is selected from any one of nano-calcium carbonate, talc, hollow glass microspheres, and glass fiber, or a combination of more than one of them.
[0037] In some feasible embodiments, the toughening agent is selected from one or more of Surlyn resin (produced by DuPont with the product brand PC8920) and ethylene-methyl acrylate copolymer.
[0038] In order to solve the technical problem raised by the present application, the present application also provides a method for preparing a plastic with high corrosion resistance, comprising the following steps:
[0039] Step 401. Ingredients: Weigh each component according to the preset target ratio;
[0040] Step 402: Primary mixing: silicone, anhydrous ethanol, and an antiseptic modifier are placed in an ultrasonic dispersing vessel according to a preset target ratio, and dispersed at room temperature and 15 kHz for 15 minutes to obtain a first mixed material.
[0041] Step 403. Secondary mixing: Polypropylene resin base material, dispersant, toughening agent, and filler are sequentially placed into a high-speed dispersing vessel in a predetermined target ratio and dispersed at room temperature and 1800-2200 rpm for 15 minutes. During the high-speed dispersion process, the first mixture prepared in the primary mixing is sprayed into the high-speed dispersing vessel via an atomizer. After dispersion is complete, a second mixture is obtained.
[0042] Step 404. The second mixture prepared in the secondary mixing is fed into a twin-screw extruder, and rubber strips are extruded at a mixing temperature of 105°C-200°C and a die pressure of -0.08 MPa. The rubber strips are sequentially cooled, dried, and granulated to obtain a high-corrosion-resistant plastic product.
[0043] Compared with the prior art, this application has the following beneficial effects:
[0044] The present application provides a high-corrosion-resistant plastic and a preparation method thereof, wherein the plastic is composed of a polypropylene resin base material, a dispersant, a toughening agent, a filler, silicone and an anti-corrosion modifier, and the anti-corrosion modifier is composed of a surface-fluorinated nano-silica-multi-walled carbon nanotube composite and an amino-grouped nanocrystalline cellulose. By optimizing the interface characteristics of the first component and the chemical activity of the second component, a multi-level synergistic anti-corrosion network is constructed in the polypropylene resin base material: after the first component is fluorinated, its hydrophobicity and chemical stability are significantly enhanced, and the three-dimensional skeleton formed by the multi-walled carbon nanotubes and nano-silica can physically block the penetration of acid / alkali / salt media and inhibit the breakage of molecular chains caused by ultraviolet rays; the amino functional group of the second component is bonded to the polypropylene base material and the first component through hydrogen bonds and covalent bonds, effectively improving the interface bonding strength of the components in the polypropylene resin base material, and at the same time, its rod-like structure can disperse stress and inhibit the propagation of microcracks. The synergistic effect of the two complements the rigid skeleton of the first component and the flexible, reinforced phase of the second component. The fluorinated surface promotes uniform dispersion of the first component, while the aminated second component further stabilizes the dispersion through chemical crosslinking, forming a dense, corrosion-resistant barrier within the matrix. This approach offers excellent corrosion resistance, stable mechanical properties, and effectively extends the service life of plastic products, making it easy to implement and scale up. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a model diagram of the cooperation between the first component and the second component in the preparation process of a high corrosion resistance plastic of the present application;
[0046] Figure 2 This is a SEM image of the first component in Example 2 of the present application.
[0047] Figure 3 This is an SEM image of the first component and the second component after fluorination in Example 2 of the present application after compounding in a preset ratio (i.e., the anti-corrosion modifier). DETAILED DESCRIPTION
[0048] Combine Figure 1-3 The contents shown in Examples 1-3 and Comparative Examples 1-5 further illustrate the technical solutions provided by this application.
[0049] The multi-walled carbon nanotubes are hydroxylated multi-walled carbon nanotubes, and the median inner diameter of the multi-walled carbon nanotubes is 4 nm, the median outer diameter is 9 nm, and the median length is 52 μm.
[0050] Furthermore, multi-walled carbon nanoparticles were purchased from Bailingwei Technology Co., Ltd.
[0051] The filler is prepared by compounding nano calcium carbonate, talcum powder and glass fiber in a mass ratio of 3:3:1.
[0052] The toughening agent is selected from ethylene-methyl acrylate copolymer.
[0053] Nanocrystalline cellulose was prepared by TEMPO oxidation.
[0054] Example 1
[0055] (1) The preparation method of nano-silica-multi-walled carbon nanotube composite comprises the following steps:
[0056] Step 101. Multi-walled carbon nanotubes and ultrapure water are placed in an ultrasonic reactor in a volume ratio of 1:155, and dispersed for 35 minutes at room temperature and an ultrasonic frequency of 18 kHz to obtain activated multi-walled carbon nanotubes.
[0057] Step 102. The activated multi-walled carbon nanotubes prepared in step 101 are transferred to a stirred tank. A silicon source is added dropwise to the activated multi-walled carbon nanotubes at room temperature and 1300 rpm. The volume ratio of the activated multi-walled carbon nanotubes to the silicon source is 1:10. After the silicon source is added, the reaction system is transferred to an ultrasonic reactor and reacted at room temperature, -0.01 MPa, and 23 kHz for 2 hours to obtain a crude first component.
[0058] Step 103. The crude product of the first component prepared in step 102 is transferred to a magnetic stirring vessel and stabilized at room temperature and 350 rpm for 12 hours to obtain a stabilized crude product of the first component;
[0059] Step 104. The stabilized crude first component prepared in step 103 is transferred to a centrifuge, the supernatant is removed, and the lower solid phase is washed with anhydrous ethanol, dried and ground to obtain the finished first component.
[0060] Wherein, in step 102, the silicon source is obtained by mixing deionized water, anhydrous ethanol, and tetraethyl silicate in a mass ratio of 1:3.5:4.2.
[0061] (2) Surface fluorination modification of the first component (nano-silica-multi-walled carbon nanotube composite) includes the following steps:
[0062] Step 201. The first component and anhydrous ethanol are sequentially added into an ultrasonic dispersion kettle at a mass ratio of 1:20, and dispersed for 20 minutes at room temperature and an ultrasonic frequency of 18 kHz to 20 kHz to obtain the activated first component;
[0063] Step 202. The activated first component prepared in step 201, ultrapure water, acetic acid, and perfluorooctyltriethoxysilane are sequentially added to a stirred tank, and the mixture is reacted in a water bath at 60° C. and 560 rpm for 5 hours to obtain a crude fluorinated first component.
[0064] Step 203. The crude fluorinated first component prepared in step 202 is transferred to a centrifuge, the supernatant is removed, and the lower solid phase is washed, filtered, and dried in sequence to obtain the finished fluorinated first component.
[0065] (3) The preparation method of the second component comprises the following steps:
[0066] Step 301. Nanocellulose crystals and anhydrous ethanol are placed in an ultrasonic reactor in a mass ratio of 1:15, and dispersed for 40 minutes at room temperature and an ultrasonic frequency of 18 kHz to obtain activated nanocellulose crystals.
[0067] Step 302: Transfer the activated nanocellulose crystals prepared in step 301 to a centrifuge, centrifuge at 8000 rpm, remove the supernatant, and retain the solid phase at the bottom.
[0068] Step 303. The lower solid phase obtained by centrifugation in step 302, anhydrous ethanol, hexadecyltrimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine and ammonia water are sequentially added into a magnetic stirring kettle in a mass ratio of 1:15:5:5:2, and reacted for 2 hours in a nitrogen atmosphere, a water bath at 42°C, and 2250 rpm. The mixture is then filtered, washed, and dried to obtain the second component product.
[0069] (4) A method for preparing a plastic with high corrosion resistance, comprising the following steps:
[0070] Step 401. Ingredients: According to the component table shown in Table 1, weigh each component and set aside;
[0071] Step 402. Primary mixing: According to the component list shown in Table 1, silicone, anhydrous ethanol, and anticorrosive modifier are placed in an ultrasonic dispersing kettle, and dispersed at room temperature and 15 kHz for 15 minutes to obtain a first mixed material;
[0072] Step 403. Secondary Mixing: According to the components shown in Table 1, the polypropylene resin base material, dispersant, toughening agent, and filler are placed in a high-speed dispersing vessel in this order and dispersed at room temperature and 1900 rpm for 15 minutes. During the high-speed dispersion process, the first mixture prepared in the primary mixing is sprayed into the high-speed dispersing vessel via an atomizer. After dispersion is complete, a second mixture is obtained.
[0073] Step 404. Mixing and extrusion: The second mixture prepared in the secondary mixing is fed into a twin-screw extruder, and a rubber strip is extruded at a mixing temperature of 105°C-200°C and a die pressure of -0.08 MPa. The rubber strip is sequentially cooled, dried, and granulated to obtain a highly corrosion-resistant plastic product.
[0074] Among them, the temperature of the feeding section of the twin-screw extruder is 105°C, the temperature of the plasticizing section is 120°C, the temperature of the compression section is 165°C, the temperature of the homogenizing section is 180°C, and the temperature of the extrusion section is 195°C.
[0075] Among them, the temperature of the feeding section of the twin-screw extruder is 105°C, the temperature of the plasticizing section is 120°C, the temperature of the compression section is 165°C, the temperature of the homogenizing section is 180°C, and the temperature of the extrusion section is 195°C.
[0076] Example 2
[0077] (1) The preparation method of nano-silica-multi-walled carbon nanotube composite comprises the following steps:
[0078] Step 101. Multi-walled carbon nanotubes and ultrapure water are placed in an ultrasonic reactor in a volume ratio of 1:170, and dispersed for 35 minutes at room temperature and an ultrasonic frequency of 19 kHz to obtain activated multi-walled carbon nanotubes.
[0079] Step 102. The activated multi-walled carbon nanotubes prepared in step 101 are transferred to a stirred tank. A silicon source is added dropwise to the activated multi-walled carbon nanotubes at room temperature and 1400 rpm. The volume ratio of the activated multi-walled carbon nanotubes to the silicon source is 1:13. After the silicon source is added, the reaction system is transferred to an ultrasonic reactor and reacted at room temperature, -0.01 MPa, and 23 kHz for 3 hours to obtain a crude first component.
[0080] Step 103. The crude first component prepared in step 102 is transferred to a magnetic stirring vessel and stabilized at room temperature and 400 rpm for 15 hours to obtain a stabilized crude first component.
[0081] Step 104. The stabilized crude first component prepared in step 103 is transferred to a centrifuge, the supernatant is removed, and the lower solid phase is washed with anhydrous ethanol, dried and ground to obtain the finished first component.
[0082] In step 102, the silicon source is obtained by mixing deionized water, anhydrous ethanol, and tetraethyl silicate in a mass ratio of 1:5.5:6.5.
[0083] (2) Surface fluorination modification of the first component (nano-silica-multi-walled carbon nanotube composite) includes the following steps:
[0084] Step 201. The first component and anhydrous ethanol are sequentially added into an ultrasonic dispersion kettle at a mass ratio of 1:23, and dispersed for 20 minutes at room temperature and an ultrasonic frequency of 18 kHz to 20 kHz to obtain the activated first component;
[0085] Step 202. The activated first component prepared in step 201, ultrapure water, acetic acid, and perfluorooctyltriethoxysilane are sequentially added to a stirred tank, and the mixture is reacted in a water bath at 75°C and 650 rpm for 7 hours to obtain a crude fluorinated first component.
[0086] Step 203. The crude fluorinated first component prepared in step 202 is transferred to a centrifuge, the supernatant is removed, and the lower solid phase is washed, filtered, and dried in sequence to obtain the finished fluorinated first component.
[0087] (3) The preparation method of the second component comprises the following steps:
[0088] Step 301. Nanocellulose crystals and anhydrous ethanol are sequentially added into an ultrasonic reactor at a mass ratio of 1:17, and dispersed at room temperature and an ultrasonic frequency of 19 kHz for 40 minutes to obtain activated nanocellulose crystals;
[0089] Step 302: Transfer the activated nanocellulose crystals prepared in step 301 to a centrifuge, centrifuge at 9000 rpm, remove the supernatant, and retain the solid phase at the bottom.
[0090] Step 303. The lower solid phase obtained by centrifugation in step 302, anhydrous ethanol, hexadecyltrimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine and ammonia water are placed in a magnetic stirring kettle in a mass ratio of 1:16:6:6:3, and reacted for 3 hours in a nitrogen atmosphere, a water bath at 45°C, and 2500 rpm. The mixture is then filtered, washed, and dried to obtain the second component product.
[0091] (4) A method for preparing a plastic with high corrosion resistance, comprising the following steps:
[0092] Step 401. Ingredients: According to the component table shown in Table 1, weigh each component and set aside;
[0093] Step 402. Primary mixing: According to the component list shown in Table 1, silicone, anhydrous ethanol, and anticorrosive modifier are placed in an ultrasonic dispersing kettle, and dispersed at room temperature and 15 kHz for 15 minutes to obtain a first mixed material;
[0094] Step 403. Secondary mixing: Polypropylene resin base, dispersant, toughening agent, and filler are sequentially placed into a high-speed dispersing vessel in a predetermined target ratio and dispersed at room temperature and 2000 rpm for 15 minutes. During the high-speed dispersion process, the first mixture prepared in the primary mixing step is sprayed into the high-speed dispersing vessel via an atomizer. After dispersion is complete, a second mixture is obtained.
[0095] Step 404. Mixing and extrusion: The second mixture prepared in the secondary mixing is fed into a twin-screw extruder, and a rubber strip is extruded at a mixing temperature of 105°C-200°C and a die pressure of -0.08 MPa. The rubber strip is sequentially cooled, dried, and granulated to obtain a highly corrosion-resistant plastic product.
[0096] Among them, the temperature of the feeding section of the twin-screw extruder is 105°C, the temperature of the plasticizing section is 120°C, the temperature of the compression section is 165°C, the temperature of the homogenizing section is 180°C, and the temperature of the extrusion section is 195°C.
[0097] Example 3
[0098] (1) The preparation method of nano-silica-multi-walled carbon nanotube composite comprises the following steps:
[0099] Step 101. Multi-walled carbon nanotubes and ultrapure water are placed in an ultrasonic reactor in a volume ratio of 1:180, and dispersed for 35 minutes at room temperature and an ultrasonic frequency of 20 kHz to obtain activated multi-walled carbon nanotubes.
[0100] Step 102. The activated multi-walled carbon nanotubes prepared in step 101 are transferred to a stirred tank. A silicon source is added dropwise to the activated multi-walled carbon nanotubes at room temperature and 1600 rpm. The volume ratio of the activated multi-walled carbon nanotubes to the silicon source is 1:15. After the silicon source is added, the reaction system is transferred to an ultrasonic reactor and reacted at room temperature, -0.01 MPa, and 25 kHz for 5 hours to obtain a crude first component.
[0101] Step 103. The crude first component prepared in step 102 is transferred to a magnetic stirring vessel and stabilized at room temperature and 600 rpm for 24 hours to obtain a stabilized crude first component.
[0102] Step 104. The stabilized crude first component prepared in step 103 is transferred to a centrifuge, the supernatant is removed, and the lower solid phase is washed with anhydrous ethanol, dried and ground to obtain the finished first component.
[0103] In step 102, the silicon source is obtained by mixing deionized water, anhydrous ethanol, and tetraethyl silicate in a mass ratio of 1:5.5:6.5.
[0104] (2) Surface fluorination modification of the first component (nano-silica-multi-walled carbon nanotube composite) includes the following steps:
[0105] Step 201. The first component and anhydrous ethanol are sequentially added into an ultrasonic dispersion vessel at a mass ratio of 1:25, and dispersed for 20 minutes at room temperature and an ultrasonic frequency of 20 kHz to obtain the activated first component;
[0106] Step 202. The activated first component prepared in step 201, ultrapure water, acetic acid, and perfluorooctyltriethoxysilane are sequentially added to a stirred tank, and reacted in a water bath at 85°C and 800 rpm for 10 hours to obtain a crude fluorinated first component.
[0107] Step 203. The crude fluorinated first component prepared in step 202 is transferred to a centrifuge, the supernatant is removed, and the lower solid phase is washed, filtered, and dried in sequence to obtain the finished fluorinated first component.
[0108] (3) The preparation method of the second component comprises the following steps:
[0109] Step 301. Nanocellulose crystals and anhydrous ethanol are sequentially added into an ultrasonic reactor at a mass ratio of 1:20, and dispersed at room temperature and an ultrasonic frequency of 20 kHz for 40 minutes to obtain activated nanocellulose crystals;
[0110] Step 302: Transfer the activated nanocellulose crystals prepared in step 301 to a centrifuge, centrifuge at 10,000 rpm, remove the supernatant, and retain the solid phase at the bottom.
[0111] Step 303. The lower solid phase obtained by centrifugation in step 302, anhydrous ethanol, hexadecyltrimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine and ammonia water are placed in a magnetic stirring kettle in a mass ratio of 1:18:8:8:5, and reacted for 5 hours in a nitrogen atmosphere, a water bath at 50°C, and 2800 rpm. The mixture is then filtered, washed, and dried to obtain the second component product.
[0112] (4) A method for preparing a plastic with high corrosion resistance, comprising the following steps:
[0113] Step 401. Ingredients: According to the component table shown in Table 1, weigh each component and set aside;
[0114] Step 402. Primary mixing: According to the component list shown in Table 1, silicone, anhydrous ethanol, and anticorrosive modifier are placed in an ultrasonic dispersing kettle, and dispersed at room temperature and 15 kHz for 15 minutes to obtain a first mixed material;
[0115] Step 403. Secondary mixing: Polypropylene resin base, dispersant, toughening agent, and filler are sequentially placed into a high-speed dispersing vessel in a predetermined target ratio and dispersed at room temperature and 2200 rpm for 15 minutes. During the high-speed dispersion process, the first mixture prepared in the primary mixing step is sprayed into the high-speed dispersing vessel via an atomizer. After dispersion is complete, a second mixture is obtained.
[0116] Step 404. Mixing and extrusion: The second mixture prepared in the secondary mixing is fed into a twin-screw extruder, and a rubber strip is extruded at a mixing temperature of 105°C-200°C and a die pressure of -0.08 MPa. The rubber strip is sequentially cooled, dried, and granulated to obtain a highly corrosion-resistant plastic product.
[0117] Among them, the temperature of the feeding section of the twin-screw extruder is 105°C, the temperature of the plasticizing section is 120°C, the temperature of the compression section is 165°C, the temperature of the homogenizing section is 180°C, and the temperature of the extrusion section is 195°C.
[0118] Comparative Example 1
[0119] The difference between Comparative Example 1 and Example 2 is that after all the anti-corrosion modifiers are removed, polypropylene resin base material and filler are used to supplement them respectively, and the other components and process steps remain unchanged.
[0120] Comparative Example 2
[0121] The difference between Comparative Example 2 and Example 2 is that after the first component in the anti-corrosion modifier is completely removed, it is supplemented with a polypropylene resin base material and a filler respectively, and the remaining components and process steps remain unchanged.
[0122] Comparative Example 3
[0123] The difference between Comparative Example 3 and Example 2 is that the second component in the anti-corrosion modifier is completely removed and then supplemented with fillers, while the remaining components and process steps remain unchanged.
[0124] Comparative Example 4
[0125] The difference between Comparative Example 4 and Example 2 is that the fluorination treatment process step of the first component is eliminated, and the process steps of the other components remain unchanged.
[0126] Comparative Example 5
[0127] The difference between Comparative Example 5 and Example 2 is that the second component is replaced by an equal amount of ordinary nanocrystalline cellulose, and the other components and process steps remain unchanged.
[0128] Table 1 Components of Examples 1-3 and Comparative Examples 1-5
[0129]
[0130] Table 1
[0131]
[0132] The high corrosion resistance plastic products prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to the following tests:
[0133] Test 1. According to ASTM B117-2016 "Salt Spray Corrosion Test Standard", the high corrosion resistance plastic products prepared in Examples 1-3 and Comparative Examples 1-5 were made into corresponding experimental pieces and then subjected to salt spray resistance testing.
[0134] Test 2. According to ASTM B117-2016 "Electrochemical Impedance Test", the high corrosion resistance plastic products prepared in Examples 1-3 and Comparative Examples 1-5 were made into corresponding experimental pieces and then subjected to electrochemical impedance spectroscopy.
[0135] Test 3. According to HB 8402-2013 "Test Method for Chemical Resistance of Plastics", the high corrosion resistance plastic products prepared in Examples 1-3 and Comparative Examples 1-5 were made into corresponding experimental pieces and then subjected to acid and alkali resistance tests.
[0136] Test 4. According to ISO 6270-2 "Wet and hot environment test method", the high corrosion resistance plastic products prepared in Examples 1-3 and Comparative Examples 1-5 were made into corresponding experimental pieces and then subjected to stability testing.
[0137] Test 5. In accordance with ASTM D638-2022, ASTM D790-2017, and ASTM D256-2023, the highly corrosion-resistant plastic products prepared in Examples 1-3 and Comparative Examples 1-5 were fabricated into corresponding test pieces. The tensile strength and elongation at break, flexural modulus, impact strength, and compressive strength of the test pieces were measured to evaluate their mechanical properties.
[0138] The test results are shown in Table 2 below.
[0139] Table 2 Test results of Examples 1-3 and Comparative Examples 1-5
[0140]
[0141] Table 2: Test results of Examples 1-3 and Comparative Examples 1-5
[0142]
[0143] From the above test results, it can be seen that in Examples 1-3, an antiseptic modifier consisting of a first component and a second component is introduced into the PP resin matrix. The first component forms a nano-silica layer on the surface of the multi-walled carbon nanotubes through hydrolysis of the silicon source, and the surface of the multi-walled carbon nanotubes is covered with C-F bonds after fluorination; the second component introduces -NH2 groups on the surface of cellulose through a silane coupling agent. Since nanocrystalline cellulose has a rod-like structure, it can form a three-dimensional network structure in the PP resin matrix after being compounded with the first component. By simultaneously introducing the first component and the second component into the PP resin matrix, the nano-silica layer formed on the surface of the multi-walled carbon nanotubes can protect the cellulose in the PP resin matrix. The pores are filled to form a dense physical anti-corrosion barrier in the PP resin matrix, which blocks the penetration of corrosive media. During the PP resin mixing process, the aminated nanocrystalline cellulose will be secondary connected with the nano-silica-multi-walled carbon nanotube composite to form a three-dimensional network structure. On the one hand, the various components in the PP resin matrix can be mechanically meshed through the three-dimensional network structure, thereby significantly improving the connection performance between the various components. On the other hand, after the nano-silica-multi-walled carbon nanotubes are dispersed, they form a conductive network in the PP resin matrix, reducing the risk of local electrochemical corrosion. The amine groups in the PP resin matrix react with the acidic medium to generate NH3 + , thereby forming a passivation layer and delaying the corrosion reaction.
[0144] In Comparative Example 1, after all the anti-corrosion modifiers were removed, the PP resin matrix lacked the physical barrier of the first component and the chemical passivation of the second component, and the corrosive medium directly eroded the matrix (failure in salt spray for 200 hours, HCl swelling +6.5%).
[0145] Furthermore, there is no reinforcement phase in the PP resin matrix, and the tensile strength is only 18.3 MPa.
[0146] In Comparative Example 2, after the first component of the anticorrosive modifier is completely removed, the PP resin matrix has no physical barrier of the first component, and the corrosive medium can penetrate quickly (salt spray for 650 hours, low frequency impedance 0.6×10 6 Ω·cm 2 );
[0147] Furthermore, the lack of rod-shaped amino nanocrystals in the PP resin matrix makes it difficult to form a disordered three-dimensional network structure, and the mechanical meshing effect of the components in the system is weakened, with a bending modulus of 1.65 GPa.
[0148] In Comparative Example 3, after the second component in the anti-corrosion modifier was completely removed, the PP resin matrix had no amine group of the second component to neutralize the acidic medium, and HCl corrosion was aggravated (mass change +3.2%).
[0149] Furthermore, the rigid structure of the first component resulted in an elongation at break of only 95.0%.
[0150] In Comparative Example 4, the fluorination process of the first component is missing, and the hydrophobicity of the PP resin is insufficient: water molecules are easily adsorbed (salt spray time 800 hours, impedance 0.7×10 6 Ω·cm 2 ).
[0151] Furthermore, the interface bonding of the unfluorinated first component is weak, and SiO2 on the surface of the multi-walled carbon nanotubes is easily detached during the mixing process, thereby reducing the filling effect of the first component and allowing the corrosive medium to penetrate quickly.
[0152] In Comparative Example 5, the second component was replaced with an equal amount of ordinary nanocrystalline cellulose. The PP resin matrix had no amino function and could not neutralize H + , HCl mass change rate +2.7%.
[0153] Furthermore, the unaminated cellulose has poor dispersibility and is difficult to form a disordered three-dimensional network structure. The mechanical meshing effect of the components in the system is weakened, and the impact strength is only 5.9 kJ / m 2 .
[0154] The present application provides a high corrosion resistance plastic and a preparation method thereof, wherein the plastic is composed of a polypropylene resin base material, a dispersant, a toughening agent, a filler, silicone and an anti-corrosion modifier, and the anti-corrosion modifier is composed of a surface fluorinated nano-silica-multi-walled carbon nanotube composite and an amino-grouped nanocrystalline cellulose. By optimizing the interface characteristics of the first component and the chemical activity of the second component, a multi-level synergistic anti-corrosion network is constructed in the polypropylene resin base material: after the first component is fluorinated, its hydrophobicity and chemical stability are significantly enhanced, and the three-dimensional skeleton formed by the multi-walled carbon nanotubes and the nano-silica can physically block the penetration of acid / alkali / salt media; the amino functional group of the second component is bonded to the polypropylene base material and the first component through hydrogen bonds and covalent bonds, effectively improving the interfacial bonding strength of the components in the polypropylene resin base material, having the advantages of excellent corrosion resistance, stable mechanical properties, long service life, and easy promotion and implementation.
[0155] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal description of the claims, or if they include equivalent structural elements that are not substantially different from the literal description of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A high corrosion resistance plastic, characterized in that: The composition is composed of the following components by weight: 55-65 parts of polypropylene resin base material, 2-5 parts of dispersant, 5-8 parts of toughening agent, 8-10 parts of filler, 8-10 parts of silicone and 15-20 parts of anti-corrosion modifier; The anti-corrosion modifier is obtained by mixing the first component and the second component in a mass ratio of (2.2-3.5):1; The first component is a nano-silica-multi-walled carbon nanotube composite; The second component is aminated nanocrystalline cellulose; The first component is surface-fluorinated.
2. A highly corrosion-resistant plastic according to claim 1, characterized in that: The preparation method of the first component comprises the following steps: Step 101. Multi-walled carbon nanotubes and ultrapure water are placed in an ultrasonic reactor in a volume ratio of 1:(150-180) and dispersed for 35 minutes at room temperature and an ultrasonic frequency of 18 kHz to 20 kHz to obtain activated multi-walled carbon nanotubes. Step 102. The activated multi-walled carbon nanotubes prepared in step 101 are transferred to a stirred tank. A silicon source is added dropwise to the activated multi-walled carbon nanotubes at room temperature and 1200-1600 rpm. After the silicon source is added, the reaction system is transferred to an ultrasonic reactor and reacted at room temperature, -0.01 MPa, and 22-25 kHz for 2-5 hours to obtain a crude first component. Step 103. Transfer the crude first component prepared in step 102 to a magnetic stirring vessel and stabilize it at room temperature and 300-600 rpm for 12-24 hours to obtain a stabilized crude first component. Step 104. The stabilized crude first component prepared in step 103 is transferred to a centrifuge, the supernatant is removed, and the lower solid phase is washed with anhydrous ethanol, dried and ground to obtain the finished first component.
3. The high corrosion resistance plastic according to claim 2, characterized in that: In step 101 , the multi-walled carbon nanotubes are hydroxylated multi-walled carbon nanotubes, and the inner diameter of the multi-walled carbon nanotubes is 3 nm to 5 nm, the outer diameter is 8 nm to 15 nm, and the length is 48 μm to 56 μm.
4. The high corrosion resistance plastic according to claim 2, characterized in that: In step 102, the silicon source is obtained by mixing deionized water, anhydrous ethanol, and tetraethyl silicate in a mass ratio of 1: (3.5-5.5): (4.2-6.5).
5. The high corrosion resistance plastic according to claim 2, characterized in that: In step 102 , the volume ratio of the silicon source to the activated multi-walled carbon nanotubes is 1:(10-15).
6. The high corrosion resistance plastic according to claim 1, characterized in that: The surface fluorination modification treatment of the first component comprises the following steps: Step 201. The first component and anhydrous ethanol are sequentially added into an ultrasonic dispersion vessel at a mass ratio of 1:(20-25), and dispersed for 20 minutes at room temperature and an ultrasonic frequency of 18 kHz to 20 kHz to obtain the activated first component; Step 202. The activated first component prepared in step 201, ultrapure water, acetic acid, and perfluorooctyltriethoxysilane are sequentially added to a stirred tank, and reacted in a water bath at 60°C-85°C and 500-800 rpm for 5-10 hours to obtain a crude fluorinated first component. Step 203. The crude fluorinated first component prepared in step 202 is transferred to a centrifuge, the supernatant is removed, and the lower solid phase is washed, filtered, and dried in sequence to obtain the finished fluorinated first component.
7. The high corrosion resistance plastic according to claim 1, characterized in that: The preparation method of the second component comprises the following steps: Step 301. Nanocellulose crystals and anhydrous ethanol are sequentially added into an ultrasonic reactor at a mass ratio of 1:(15-20), and dispersed at room temperature and an ultrasonic frequency of 18 kHz to 20 kHz for 40 minutes to obtain activated nanocellulose crystals; Step 302: Transfer the activated nanocellulose crystals prepared in step 301 to a centrifuge, centrifuge at 8000-10000 rpm, remove the supernatant, and retain the solid phase at the bottom; Step 303. The lower solid phase obtained by centrifugation in step 302, anhydrous ethanol, hexadecyltrimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine and ammonia water are sequentially added into a magnetic stirring kettle, reacted for 1 h to 5 h in a nitrogen atmosphere, a water bath at 40°C to 50°C, and 2200 rpm to 2800 rpm, and then filtered, washed and dried in sequence to obtain the second component product.
8. The high corrosion resistance plastic according to claim 7, characterized in that: In step 303, the mass ratio of the lower solid phase, anhydrous ethanol, hexadecyltrimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine and ammonia water is 1:(15-18):(5-8):(5-8):(2-5).
9. The high corrosion resistance plastic according to claim 1, characterized in that: The filler is selected from any one of nano calcium carbonate, talc, hollow glass microspheres, and glass fiber, or a combination of more than one of the above.
10. A method for preparing a plastic with high corrosion resistance according to any one of claims 1 to 9, characterized in that: The following steps are involved: Ingredients: weigh each component according to the preset target ratio; Primary mixing: according to the preset target ratio, silicone, anhydrous ethanol and anti-corrosion modifier are put into an ultrasonic dispersing kettle, and dispersed for 15 minutes at room temperature and 15KHz to obtain the first mixed material; Secondary mixing: According to the preset target ratio, the polypropylene resin base material, dispersant, toughening agent and filler are sequentially put into a high-speed dispersing kettle, and dispersed at room temperature and 1800-2200 rpm for 15 minutes. During the high-speed dispersion process, the first mixed material prepared in the primary mixing is sprayed into the high-speed dispersing kettle through an atomizing device. After the dispersion is completed, the second mixed material is obtained; Mixing and extrusion: The second mixed material prepared in the secondary mixing is fed into a twin-screw extruder, and rubber strips are extruded under the conditions of a mixing temperature of 105°C-200°C and a die pressure of -0.08MPa. The rubber strips are sequentially cooled, dried, and granulated to obtain a high-corrosion-resistant plastic product.
Citation Information
Patent Citations
High strength and high toughness modified poly-propylene material
CN101020775A
Novel method for coating carbon nano-tube with silicon dioxide
CN101318644A
High-flame-retardation heat-resistant modified natural rubber composite
CN105754156A
Microcrystalline cellulose hydrolysis preparation method, conductive flame-retardant composite material and preparation method of conductive flame-retardant composite material
CN107857820A
Carbon nanotube heterozygote modified polyolefin insulation reinforcement and preparation method thereof
CN111909446A